A Review of the Prevention of Mother-to-Child Transmission of Human T-Cell Lymphotrophic Virus Type 1 (HTLV-1) With a Proposed Management Algorithm - Barr, Rachael S.; Drysdale, Simon B.; Boullier, Mary; Lyall, Hermione; Cook, Lucy; Collins, Graham P.; Kelly, Dominic F.; Phelan, Lorna; Taylor, Graham P. (Frontiers in Medicine, 2022)
Human T cell lymphotropic virus type 1 (HTLV-1) is a human retrovirus that is endemic in a number of regions across the world. There are an estimated 5-10 million people infected worldwide. Japan is currently the only country with a national antenatal screening programme in place. HTLV-1 is primarily transmitted sexually in adulthood, however it can be transmitted from mother-to-child perinatally. This can occur transplacentally, during the birth process or via breastmilk. If HTLV-1 is transmitted perinatally then the lifetime risk of adult T cell leukaemia/lymphoma rises from 5% to 20%, therefore prevention of mother-to-child transmission of HTLV-1 is a public health priority. There are reliable immunological and molecular tests available for HTLV-1 diagnosis during pregnancy and screening should be considered on a country by country basis. Further research on best management is needed particularly for pregnancies in women with high HTLV-1 viral load. A first step would be to establish an international registry of cases and to monitor outcomes for neonates and mothers. We have summarised key risk factors for mother-to-child transmission of HTLV-1 and subsequently propose a pragmatic guideline for management of mothers and infants in pregnancy and the perinatal period to reduce the risk of transmission. This is clinically relevant in order to reduce mother-to-child transmission of HTLV-1 and it’s complications.